Lactone Derivatives Produced by a Phaeoacremonium sp., an Endophytic Fungus from Senna spectabilis - Silva, Geraldo H.; Zeraik, Maria L. [UNESP]; De Oliveira, Camila M.; Teles, Helder L.; Trevisan, Henrique C. [UNESP]; Pfenning, Ludwig H.; Nicolli, Camila P.; Young, Maria C. M.; Mascarenhas, Yvonne P.; Abreu, Lucas M.; Saraiva, Amanda C. [UNESP]; Medeiros, Alexandra I. [UNESP]; et al. (American Chemical Society (ACS), 2017)
Three new isoaigialones, A, B, and C (1-3), along with aigialone (4), were isolated from the crude EtOAc extract of a Phaeoacremonium sp., an endophytic fungus obtained from the leaves of Senna spectabilis. The structures of these compounds were elucidated based on the analysis of spectroscopic data. Compounds 2 and 4 were active against the phytopathogenic fungi Cladosporium cladosporioides and C. sphaerospermum. This is the first report of metabolites produced by an Phaeoacremonium sp., associated with S. spectabilis.